2022
DOI: 10.3390/app12104845
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Restraint Effect of Isolation Pile on Surface Settlement Trough Induced by Shield Tunnelling

Abstract: Isolation piles are widely used to control the influence of shield tunnelling on adjacent buildings as an effective protective measure. However, the restraint effect of isolation pile on surface settlement trough is rarely explored from the internal mechanism. Firstly, the restraint mechanism of isolation piles is investigated from the pile-soil-tunnel interaction mechanism. Secondly, based on the Melan solution and the Loganathan formula, the analytical solution of surface settlement trough under the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some scholars (Beyabanaki and Gall, 2017;Shan et al, 2021;Zhang et al, 2021;Wei et al, 2022) have conducted a deformation simulation of a shield interval under a high-speed rail-way bridge pile foundation to evaluate the control effect of isolation piles from multiple angles and concluded that isolation piles can significantly reduce the impact of the superposition effect on bridge piles caused by two-lane tunnel excavation. According to the influence mechanism of shield structure transverse channel disturbance on tunnel deformation under special circumstances such as deep coal mine and the analysis of the model of shield tunnel ultra-close crossing pile group, some scholars (Wu et al, 2021;Yu et al, 2021;Huang et al, 2022;Pan et al, 2022;Ren et al, 2022;Yuan et al, 2022) have obtained the deformation and failure mechanism of shield tunnel under special conditions. Other researchers (Dezi et al, 2012;Liu et al, 2022;Zhou et al, 2022) have established an analytical model of pile-soil interaction, introduced the deformation coordination relationship, and verified it by comparing the analytical solution with measured data to reveal the mechanical mechanism of the effect of isolation piles on the vertical dis-placement of the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars (Beyabanaki and Gall, 2017;Shan et al, 2021;Zhang et al, 2021;Wei et al, 2022) have conducted a deformation simulation of a shield interval under a high-speed rail-way bridge pile foundation to evaluate the control effect of isolation piles from multiple angles and concluded that isolation piles can significantly reduce the impact of the superposition effect on bridge piles caused by two-lane tunnel excavation. According to the influence mechanism of shield structure transverse channel disturbance on tunnel deformation under special circumstances such as deep coal mine and the analysis of the model of shield tunnel ultra-close crossing pile group, some scholars (Wu et al, 2021;Yu et al, 2021;Huang et al, 2022;Pan et al, 2022;Ren et al, 2022;Yuan et al, 2022) have obtained the deformation and failure mechanism of shield tunnel under special conditions. Other researchers (Dezi et al, 2012;Liu et al, 2022;Zhou et al, 2022) have established an analytical model of pile-soil interaction, introduced the deformation coordination relationship, and verified it by comparing the analytical solution with measured data to reveal the mechanical mechanism of the effect of isolation piles on the vertical dis-placement of the ground.…”
Section: Introductionmentioning
confidence: 99%
“…However, the necessity for mesh precision is significant when dealing with the dynamic problem of local impact load, and it is still difficult to fully reflect the local punching characteristics around the hammer. With the continuous development of numerical analysis technology, continuum-discrete coupling calculation methods, such as FDM-DEM coupling, provide a new possibility to solve the dynamic problem of local large deformation [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Displacements induced by underground volume contraction negatively affect the overlying infrastructure and nearby underground structures. As examples, piles experience lateral deflection, bending moments, settlement, and abnormal load distribution [14][15][16][17]; lifelines are sheared and disrupted [18][19][20][21]; buildings develop differential settlement and horizontal displacement [22][23][24]; and adjacent tunnels may rotate and undergo asymmetric settlement [25,26].…”
Section: Introductionmentioning
confidence: 99%